2008
DOI: 10.1111/j.1540-8159.2008.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation for Atrioventricular Nodal Reentrant Tachycardia in Young Patients: Predictors of Recurrence

Abstract: BACKGROUND Recurrence rates of AVNRT after cryoablation continue to remain high despite excellent initial success rates. Our objective was to evaluate the clinical outcomes of cryoablation for AVNRT with the 4 mm and 6 mm tip cryoablation catheters in a young population and to elicit predictors of arrhythmia recurrence. METHODS We retrospectively reviewed all patients who underwent cryoablation for AVNRT at the UCSF/Stanford Pediatric Arrhythmia Center from 1/04-2/07. RESULTS 154 patients (age 13.7 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 22 publications
4
58
0
Order By: Relevance
“…Although no difference was found about ablation end point, that is, complete SP ablation versus SP modulation, 6,22 the choice of ablation energy has been proven to influence long-term efficacy: cryoenergy was associated with a higher AVNRT recurrence rate, but the procedural risk of permanent AV block was lower 6,23,24 In accordance with previous reports, 22,25,26 we did not find any difference in long-term recurrence rates between patients with SP ablation versus SP modulation at the end of the procedure. Because the number of patients with AVNRT recurrence was low (n=22), any analysis on factors for recurrence has low statistical power.…”
Section: Discussionsupporting
confidence: 77%
“…Although no difference was found about ablation end point, that is, complete SP ablation versus SP modulation, 6,22 the choice of ablation energy has been proven to influence long-term efficacy: cryoenergy was associated with a higher AVNRT recurrence rate, but the procedural risk of permanent AV block was lower 6,23,24 In accordance with previous reports, 22,25,26 we did not find any difference in long-term recurrence rates between patients with SP ablation versus SP modulation at the end of the procedure. Because the number of patients with AVNRT recurrence was low (n=22), any analysis on factors for recurrence has low statistical power.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies in pediatric patients who have had catheter cryoablation have been reported with no thromboembolic complications. [546][547][548][549] Compared with RFCA, catheter cryoablation appears to be less thrombogenic. An in vitro study demonstrated significant damage to blood cells and platelets with RFCA compared with catheter cryoablation.…”
Section: Catheter Cryoablationmentioning
confidence: 99%
“…18 Furthermore, a recent study showed that the AVNRT recurrence rate was higher with a 4-mm tip cryoablation catheter (18%) than with a 6-mm tip cryoablation catheter (9%). 19 Thus, in the present study we compared the effect of cryoablation catheter size and length on acute and chronic left ventricular lesion sizes. We evaluated cryocatheters of 2 different sizes in porcine and canine endocardial and epicardial ablation models, and examined the acute and chronic effects of cryothermal ablation on ventricular tissue.…”
Section: Discussionmentioning
confidence: 99%